PENINGKATAN HASIL BELAJAR SISWA MELALUI METODE PEMBELAJARAN MAKE A MATCH - Khasanah, Khasanah; Nasution, Nursanita; Utari, Anna Indah; Yustantina, Eka Yunita (Akademika, 2025)
This research aims to determine the application of the Make a Match learning model in improving basic culinary learning outcomes and the quality of student learning after applying the Make a Match learning model in the Basic Culinary subject. This research involved 35 class X Catering 1 SMKN 3 Bekasi City students. The research approach used is classroom action research, which aims to apply learning strategies to natural situations. This research uses the spiral model from Kemmis and Taggart, which consists of two cycles, each using four action components: planning and acting. Observation and reflection. The data collection procedure was carried out in 3 cycles, where each cycle carried out learning using the Make a Match method. The instruments used in this classroom action research were observation sheets, learning outcomes tests, and documentation regarding the application of the Make a Match learning model, which can improve student learning outcomes in basic culinary subjects in class.